Total Anomalous Pulmonary Venous Connection in Mother and Son with a Central 22q11.2 Microdeletion - Signe Faurschou; Dorte L. Lildballe; Lisa L. Maroun; Morten Helvind; Maria Rasmussen (Case Reports in Genetics)
In this clinical report, we describe a male infant and his mother, who had similar congenital heart defects. They were both diagnosed neonatally with total anomalous pulmonary venous connection (TAPVC) in combination with other heart defects. Neither of the two had any other organ malformations or dysmorphic facial features. SNP-array identified a central 22q11.2 microdeletion in the male infant and his mother as well as in the maternal grandmother and maternal aunt. The mother and the maternal aunt additionally harbored a 15q11.2 BP1-BP2 microdeletion. The maternal grandmother was unaffected by heart disease. However, heart computed tomography scan of the maternal aunt revealed a quadricuspid aortic valve. Additionally, the maternal grandmother and the maternal aunt both had significant learning disabilities. Rarely, TAPVC has been described in patients with the common 22q11.2 microdeletions. However, to the best of our knowledge, TAPVC has not previously been reported in patients with this small central 22q11.2 microdeletion. Haploinsufficiency of TBX1 was originally thought to be the main cause of the 22q11.2 microdeletion syndrome phenotype, but TBX1 is not included in the atypical central 22q11.2 microdeletion. Previous reports have suggested an association between TAPVC and the 15q11.2 BP1-BP2 microdeletion. Our report does not support this association as the maternal aunt, who harbors both microdeletions, is unaffected by TAPVC, and the male infant affected by TAPVC does not harbor the 15q11.2 BP1-BP2 microdeletion. Our findings support that genes located in the central 22q11.2 region are important for heart development and that haploinsufficiency of these genes plays a crucial role in the development of the rare heart defect TAPVC.